الحروب الاقتصاديّة أحد أساليب الإرهاب الاقتصادي غير المنظّم (العراق نموذجاً) - قنوع, نزار; الخطيب, دريد; عاقل, منال علي (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول البحث إحدى آليّات الإرهاب الاقتصادي غير المنظّم، والذي يُعتَبر الشّكل المُكمّل للإرهاب الاقتصادي المنظّم الذي تمارسه المنظّمات الدّوليّة كصندوق النّقد الدّولي، البنك الدّولي، ومنظّمة التجّارة العالميّة، أمّا هذا الشّكل غير المنظّم للإرهاب الاقتصادي فيُمارَس من قِبَل دولة أو أكثر ضدّ دولة أخرى أو مجموعة دول ومن ممارساته، العقوبات الاقتصاديّة، والحروب الاقتصاديّة محور بحثنا. يتطرّق البحث إلى الدّوافع الحقيقيّة لحروب الدّول الكبرى لاسيما الولايات المتّحدة، ودور النّفط في تلك الحروب، وهل هي حرب من أجل النفط؟ والانتشار العسكري للقوّات الأمريكيّة في المناطق التي تمتلك موارد الطاقة في العالم، لنصل لدراسة العراق كنموذج تمّت الحرب الاقتصاديّة عليه، وبالتّالي إظهار الآثار الكارثيّة لتلك الحرب على الشّعب على الصّعيد الاجتماعي والاقتصادي، وتبيان ما هي الأسباب الحقيقية الكامنة وراء تلك الحرب، والتي كانت أسبابها، لا علاقة لها بالأسباب المُعلنة. The research discusses one of the mechanisms of the unregulated economic terror, which is considered as the supplementing shape of regulated economic terror practiced by international organizations such as the IMF, World Bank, WTO, but this shape of unregulated economic terror is practiced by a state or more against another state or group of states, and the economic sanctions, and economic wars, which is the focus of our research, are part of its practices. The research talks about the real motives of the great nations' wars especially the USA and the role of oil in those wars and is it war for oil? And the military deployment of US forces in areas which possess energy resources in the world. to get to study Iraq as a model in which an economical war had broken out on it, and thus show the disastrous effects of the war on the people at the social and economic levels, and to identify what are the real reasons behind the war which their causes was not related to the announced reasons.